Reproducibility, Validity, and Relative Validity of Self-Report Methods for Assessing Physical Activity in Epidemiologic Studies: Findings From the Women's Lifestyle Validation Study. Issue 4 (5th January 2022) - Al-Shaar, Laila; Pernar, Claire H; Chomistek, Andrea K; Rimm, Eric B; Rood, Jennifer; Stampfer, Meir J; Eliassen, A Heather; Barnett, Junaidah B; Willett, Walter C
Abstract: Among 683 participants in the Women's Lifestyle Validation Study (2010–2012), we evaluated the performance of a self-administered physical activity questionnaire (PAQ) and Web-based 24-hour recalls (Activities Completed Over Time in 24 Hours (ACT24)) using multiple comparison methods. Two PAQs, 4 ACT24s, two 7-day accelerometer measurements, 1 doubly labeled water (DLW) physical activity level (PAL) measure (repeated; n = 90), and 4 resting pulse rate measurements were collected over 15 months. The deattenuated correlation between the PAQ and DLW PAL was 0.41 (95% confidence interval (CI): 0.33, 0.49) for total physical activity (PA) and 0.40 (95% CI: 0.31, 0.48) for moderate-to-vigorous PA (MVPA). These correlations were similar when using accelerometry as the comparison method. Single and averaged ACT24 measurements had lower correlations with DLW and accelerometry as comparison methods. The PAQ showed inverse correlations with DLW body fat percentage and resting pulse rate. Using the method of triads, the estimated correlation of the PAQ with true total PA was 0.54 (95% CI: 0.47, 0.62) and that with true MVPA was 0.60 (95% CI: 0.52, 0.69). For averaged ACT24, the estimated correlations were 0.50 (95% CI: 0.43, 0.59) for total PA and 0.47 (95% CI: 0.39, 0.58) for MVPA, and for averaged accelerometry, these estimated correlations were 0.72 (95% CI: 0.64, 0.81) and 0.62 (95% CI: 0.53, 0.71), respectively. The PAQ provided reasonable validity for total PA and MVPA.